Associations between EFL students' L2 grit, boredom coping strategies, and emotion regulation strategies: a structural equation modeling approach - Solhi, Mehdi; Derakhshan, Ali; Ünsal, Büşra (Journal of multilingual and multicultural development, 2025)
This study intended to explore the relations between 259 Turkish EFL students' L2 grit (i.e. the persistence of effort and consistency of interest) and boredom coping strategies (i.e. cognitive approach, behavioural approach, cognitive avoidance, and behavioural avoidance) as well as the moderating role of their emotion regulation strategies, viz., reappraisal and suppression. The results of the structural equation modelling (SEM) indicated strong correlations between L2 grit and boredom coping strategies as well as emotional regulation and boredom coping strategies. Moreover, the correlation between L2 grit and emotional regulation was found moderately strong. Although L2 grit was entirely a strong predictor of boredom coping strategies, it was indicated to be a stronger predictor of cognitive approach to cope with boredom. Additionally, the results showed that L2 grit was a significant predictor of boredom coping strategies, whereas emotion regulation did not significantly moderate this prediction. Pedagogical implications are discussed regarding the significance of grit in L2 contexts.